Estudio de la composición de una película de polietileno de alta densidad, para reducir costos de fabricación garantizando propiedades mecánicas y físicas (2015)
Films of high density polyethylene (HDPE ) produced in the plastic company by extrusion blown tubular film were characterized in physical terms (density and colorimeter) and mechanical ( tensile strength and resistance to specify fatigue ), with the objective to standardize and optimize the amount of raw material used, and specifically the recovered HDPE and calcium carbonates , which are additives inexpensive. $ 1900 per kg and $ 950 per kg respectively, while HDPE and LLDPE is $ 3780 per kg and $ 3800 per kg respectively. It was determined that the 36,0% HDPE, 11,5% LLPEAD, 14,5% Economaster, 4,0% white masterdbacth and 34,0% white R-HDPE, met the mechanical requirements established for the service conditions and also a reduction of 15% of the cost of production was achieved, represented a saving of 17´161.920 million Colombian pesos annually compared with production costs to November of year 2014.